The theory of interest rates : proceedings of a conference held by the International Economic Association - Hahn, Frank; Brechling, Frank P. R.; International Economic Association (London : Macmillan ; New York : St. Martin's Press, 1965)
This study contains compilation of papers presented at a conference on the theory of interest and money organized by the International Economic Association and held at the Abbey of Royaumont from 28 March to 7 April 1962.
Includes index.
Includes bibliographical references: p. 239-241.
ne 22/01/2019
Loans
Keywords: Interest